Assises contre le racisme - Langenaken, Dominique (Bruxelles : MRAX, 1982)
Fonds VCIM
Bevat bijdragen van Mateo Alaluf, Véronique De Rudder, Alain De Wasseige, Monique Dujardin, Angel Enciso, Thérèse Gastaut, Claude Geets, Albert Jacquard, Marcel Liebman, Albert Martens, Frank Moulaert, Me Pau-Langevin, Paulette Van Gansen
Frans
Brochure